An Investigation of Silica Aerogel to Reduce Acoustic Crosstalk in CMUT Arrays - Varshitha Yashvanth; Sazzadur Chowdhury (Sensors, 2021)
This paper presents a novel technique to reduce acoustic crosstalk in capacitive micromachined ultrasonic transducer (CMUT) arrays. The technique involves fabricating a thin layer of diisocyanate enhanced silica aerogel on the top surface of a CMUT array. The silica aerogel layer introduces a highly nanoporous permeable layer to reduce the intensity of the Scholte wave at the CMUT-fluid interface. 3D finite element analysis (FEA) simulation in COMSOL shows that the developed technique can provide a 31.5% improvement in crosstalk reduction for the first neighboring element in a 7.5 MHz CMUT array. The average improvement of crosstalk level over the −6 dB fractional bandwidth was 22.1%, which is approximately 5 dB lower than that without an aerogel layer. The results are in excellent agreement with published experimental results to validate the efficacy of the new technique.